Analyse des formes onomatopées dans la bande dessinée Tandoori : un livre dans la jungle - Christasya Meyshi Sihite; Andi Wete Polili (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
Analysis of Onomatopoeic Forms in the Comic Strip Tandoori: Un Livre Dans La Jungle. This study aims to analyze and describe the different forms and meanings of onomatopoeia present in the comic strip Tandoori: Un Livre Dans La Jungle. This research uses a descriptive qualitative method, and the subject of this research is the comic strip Tandoori: Un Livre Dans La Jungle. This research uses the theory of Enckell and Rézeau (2003: 31-40), who explain that there are nine types of onomatopoeia. These are human body noises, animal noises, nature noises, noises produced by manufactured objects, everyday noises, social noises, leisure noises, noise nature, noise color, and noise and abstraction. After observation, 134 onomatopoeias were found. The results of the data analysis made it possible to classify human body noises (23.13%), animal noises (20.14%), nature noises (10. 44%), noises produced by manufactured objects (23.13%), noises of everyday life (6.71%), noises of social life, leisure (2.23%), nature of noise (2.98%), color of noise (7.46%) and noise and abstraction (3.73%). Data were analyzed using a descriptive method and by collecting data using a free-listening technique. The author used Miles and Huberman’s theory to analyze the data.